South African Architectural Record - (:unkn) unknown (Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1928)
South African Architectural Record
Journal of the Transvaal, Natal and Orange Free State Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors
Journals
Keywords: South African Architectural History